Power System Grid Operation Using Synchrophasor Technology - Nuthalapati, Sarma (NDR).; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book brings together successful stories of deployment of synchrophasor technology in managing the power grid. The authors discuss experiences with large scale deployment of Phasor Measurement Units (PMUs) in power systems across the world, enabling readers to take this technology into control center operations and develop good operational procedures to manage the grid better, with wide area visualization tools using PMU data. · Provides a single-source reference to the practical applications of Synchrophasor technology in operating the power grid; · Includes real case studies from utilities that have deployed the technology; · Offers an international perspective on the use of data obtained from phasor measurement units, in order to manage power grids.
Importance of Using Synchrophasor Technology in Managing the Grid -- Impact of Phasor Measurement Data Quality in Grid Operations -- Testing and Validation of Synchrophasor Devices and Applications -- Synchrophasor Technology at BPA: From Wide Area-Monitoring to Wide-Area Control -- Use of Synchrophasor Measurement Technology in China -- Identification of Signature Oscillatory Modes in ERCOT by Mining of Synchrophasor Data -- Oscillation Detection in Real-Time Operations at ERCOT -- Oscillation Detection and Mitigation Using Synchrophasor Technology in the Indian Power Grid -- Experiences of Oscillation Detection and Mitigation in Grid Operations at PEAK RC -- Online Oscillation Management at ISO New England -- Operational use of Synchro-phasor Technology for Power System Oscillations Monitoring at California ISO -- Operational Use of Synchro-phasor Technology for Wide-Area Power System Phase Angle Monitoring at California ISO -- Synchrophasor-based Linear State Estimation Techniques andApplications -- Implementation of Synchrophasor-based Linear State Estimator for Real-time Operation -- Post-Event Analysis in the ERCOT system Using Synchrophasor Data -- Validation and Tuning of Remedial Action Schemes in Indian Grid Operations Using Synchrophasor Technology -- Indian Power System Operation Utilizing Multiple HVDC and WAMS -- Model Validation using Synchrophasor Technology -- A Software Suite for Power System Stability Monitoring Based on Synchrophasor Measurements -- A Cloud-Hosted Synchrophasor Data Sharing Platform.
Keywords: Electric power production; Energy policy; Energy and state; Electrical Power Engineering; Mechanical Power Engineering; Energy Policy, Economics and Management